1971
DOI: 10.1099/00221287-68-3-263
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Carbenicillin and  -Lactamases from Gram-negative Bacteria

Abstract: The rates of hydrolysis of carbenicillin and of other penicillins and cephalosporins by nine different P-lactamase preparations obtained from Gram-negative bacteria were compared. Enzymes produced by Klebsiella strains, most active against penicillins, as well as P-lactamases synthesized by Escherichia coli and Proteus tnirabilis strains hydrolysed carbenicillin, although at relatively lower rates than ampicillin or cephaloridine. In contrast, carbenicillin was extremely resistant to /3-lactamases with a predo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1973
1973
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…Resistance to kanamycin and neomycin is also mediated by an enzyme, aminoglycoside-3'-phosphotransferase (3), but there is evidence that the resistance to tetracycline may be due to a change in permeability of the cell walls of the R+ bacteria (38). Some authors have suggested that carbencillin resistance in RI strains ofPseudomonas aeruginosa may be due, in part, to changes in cell wall permeability (4,36,37). P. aeruginosa possessing a mutant of RP1 (RPl-1) showed resistance to carbenicillin without ,8-lactamase production, and it was suggested that resistance was due to modification of the cell wall (10).…”
mentioning
confidence: 99%
“…Resistance to kanamycin and neomycin is also mediated by an enzyme, aminoglycoside-3'-phosphotransferase (3), but there is evidence that the resistance to tetracycline may be due to a change in permeability of the cell walls of the R+ bacteria (38). Some authors have suggested that carbencillin resistance in RI strains ofPseudomonas aeruginosa may be due, in part, to changes in cell wall permeability (4,36,37). P. aeruginosa possessing a mutant of RP1 (RPl-1) showed resistance to carbenicillin without ,8-lactamase production, and it was suggested that resistance was due to modification of the cell wall (10).…”
mentioning
confidence: 99%
“…of penicillin G, ampicillin and cephaloridine, whereas sensitivity to carbenicillin and 6-APA remains virtually unchanged. This reveals the stability of 6-APA and the absolute inertness of carbenicillin towards the hydrolytic activity of the S & A enzyme (Garber & Friedman, 1970;Bobrowski & Borowski, 1971;Richmond & Sykes, 1972) and shows that stability against this enzyme is necessary (though not the only prerequisite) to enable plactam drugs to act efficiently on Pseudomonas aeruginosa.…”
Section: Resultsmentioning
confidence: 88%
“…All strains of P. aeruginosa examined:so far synthesize inducible p-lactamases that are indistinguishable from one another and require high concentrations of penicillin G for optimal induction (Sabath et al 1965;Garber & Friedman, 1970;Bobrowski & Borowski, 1971;Sykes & Richmond, 1971). The purified enzyme is defined as moderate cephalosporinase (p-lactamase class Id) (Richmond & Sykes, 1972) and is inhibited by carbenicillin, cloxacillin and methicillin (Bobrowski & Borowski, 1971 ;Richmond & Sykes, 1972). The efficacy of carbenicillin (Acred et al 1967) against P.…”
Section: Introductionmentioning
confidence: 99%
“…While all the different serological groups (Winblad, I 967, 1968 ;Wauters, Le Minor & Chalon, 1971;Wauters et al 1972) of Y. enterocolitica are /3-lactamase producers, they differ from one another in the pattern of their sensitivities to /3-lactam antibiotics (Cornelis et al 1973). …”
Section: Introductionmentioning
confidence: 99%